2012
DOI: 10.1590/s0100-40422012001000029
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fipronil in bovine plasma by solid-phase extraction and liquid chromatography with ultraviolet detection

Abstract: Recebido em 7/3/12; aceito em 9/7/12; publicado na web em 25/9/12 A fast and efficient method has been developed and validated for the determination of fipronil in bovine plasma. Samples were subjected to solid-phase extraction (SPE) followed by reversed phase liquid chromatography (LC) separation, using acetonitrile/ water (60:40 v/v) as the mobile phase with a flow rate of 1.0 mL/min and ultraviolet (UV) detection at 210 nm. Ethiprole was used as the internal standard (IS). The method was found to be linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Previous results reported that after a repeated oral administration, fipronil concentrations in rat plasma were lower than the LOQ (<100ng/mL) while fipronil sulfone concentrations ranged from 1 to 2 µg/mL (Lacroix et al 2010). The LOQ of fipronil sulfone was 5 ng/mL (Cid et al 2012) and it ranged from 0.05-0.16 and 0.28-0.73 µg/mL for fipronil and fipronil sulfone, respectively (Bichon et al 2008). Blank (control group of rats) samples were spiked with 3 levels (1, 5, 10 µg/g) of each compound and were read in triplicates.…”
Section: Methods Limit Of Quantification (Loq) Precision and Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results reported that after a repeated oral administration, fipronil concentrations in rat plasma were lower than the LOQ (<100ng/mL) while fipronil sulfone concentrations ranged from 1 to 2 µg/mL (Lacroix et al 2010). The LOQ of fipronil sulfone was 5 ng/mL (Cid et al 2012) and it ranged from 0.05-0.16 and 0.28-0.73 µg/mL for fipronil and fipronil sulfone, respectively (Bichon et al 2008). Blank (control group of rats) samples were spiked with 3 levels (1, 5, 10 µg/g) of each compound and were read in triplicates.…”
Section: Methods Limit Of Quantification (Loq) Precision and Accuracymentioning
confidence: 99%
“…Also, HPLC method with UV detection (Leghait et al 2009) was used for fipronil determination in rats' plasma and showed that fipronil was actively metabolized to its sulfone derivative. The reversed-phase LC-UV (at 210 nm) was efficient in the determination of fipronil in bovine plasma after SPE extraction (SPE) (Cid et al 2012), plasma samples using GC-MS/MS (Bichon et al 2008), LC-UV/MS and GC-MS, LC-MS/MS in animal urine samples (Cravedi et al 2013), in human and rodents urine and serum sample using the liquid chromatography/time-of-flight mass spectrometer (LC/TOF-MS) (McMahen et al 2015), and in blood samples of rat and human using LC-MS/MS (Raju et al 2016). Fipronil and its residues were extracted using solid-phase microextraction (SPME; fused-silica fiber coated with 85 mm polyacrylate) (Vıĺchez et al 2001) Because of the limited studies that investigate the movement and transformation of fipronil in various internal tissues of mammals, the current study aimed to detect and determine fipronil and fipronil sulfone in tissues of internal organs of white albino rats using gas chromatography coupled with mass spectroscopy (GC-MS) after oral administration of rats of repetitive sublethal doses of fipronil for 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile phase consisted of acetonitrile: water (60:40, v/v) with a flow rate of 1.0 mL/min. The UV wavelength was set at 210 nm and the injection volume was 10 μL (22).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…It is relatively stable in water, but it´s not so stable in soil, due to its photolysis. Thus, the development of a precise, exact, rapid and efficient method of its quantification is really actual task [14][15][16].…”
Section: Fipronilmentioning
confidence: 99%